No such person - Cooney, Caroline B. (Ember, 2016)
Not long after starting their summer vacation, the Allerdons are faced with a nightmare--Lander, the oldest girl, begins dating a handsome young man, and shortly afterwards is accused of murder. Her little sister, Miranda, cannot believe Lander is guilty, and thinks her new boyfriend has something to do with the false accusations. However, the more she investigates, the more Miranda wonders if Lander really could have committed such a heinous crime.